The Effect of Energy Consumption and Renewable Energy on Economic Growth in Indonesia - Purnomo, Sodik Dwi; Wani, Nur; Suharno, Suharno; Arintoko, Arintoko; Sambodo, Herman; Badriah, Lilis Siti (International Journal of Energy Economics and Policy, 2023)
The economic growth in Indonesia showed a stable trend while the growth in energy consumption showed a declining trend. However, previous studies had revealed the existence of positive and significant relationship between energy consumption and economic growth. This study aims to analyse the effect of oil, gas, and biomass fuel consumption, road infrastructure, life expectancy, and average length of education on economic growth in Indonesia during the year of 1990-2019. This study used quantitative approach with linear regression as data analysis method. The data used are time series data from the period of 1990-2019. The result of this study showed that oil, gas, and biomass fuel consumption, as well as average length of education have a positive and significant effect, while road infrastructure and life expectancy have no effect on economic growth in Indonesia for the year of 1990-2019. This study recommends: 1) energy reserves should be improved by increasing the number of energy sources and developing more infrastructure in order to support and boost the supply of energy, 2) quality of educations should be upgraded by giving out scholarships as well as improving the educators and physical infrastructure.